ECONOMIC VIEWS AND ECONOMIC POLICY HETMAN I. S. MAZEPA (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Introduction. The article considers the activity of Hetman IS Mazepa, his government, local governments on the effective development of agriculture, handicrafts, various types of urban and rural crafts, strengthening trade and economic ties both in Ukraine and abroad. .The origin of agricultural entrepreneurship on the lands of the Cossack sergeant, manufacturing industry: iron smelting, potash, glassmaking and saltpeter is studied. Cossack and peasant farms organized according to the farm model are studied.Peculiarities of formation of a new economic system in the conditions of fierce struggle for independence of Ukraine are noted.The essence of reforming agrarian relations, organization and activity of Cossack-peasant farms, agricultural entrepreneurship of Cossack officers and the origin and development of the manufacturing industry.The purpose of the article. Сonsideration and analysis of the economic activity of Hetman IS Mazepa, his government and local authorities.The objectives of the article are to highlight the essence of the reform of agrarian relations, the organization and activities of the Cossack - peasant farms, agricultural entrepreneurship of the Cossack sergeant and the origin and development of the manufacturing industry.Results. With the development of commodity-money relations, the farms of Cossack officers, ordinary Cossacks and peasants became more and more closely connected with the market. Cossacks and peasants were among the first in Europe to apply on their lands new forms of farming, typical of the farming type. In the new forms of Cossack - peasant farms IS Mazepa saw the future of the Ukrainian state.The number of artisans of various specialties is growing in cities and towns, and industries for processing agricultural products and local raw materials are being built. Flour and distillery production is becoming more widespread. On the lands of the Cossack sergeant, in some Cossack and peasant farms manufactory-type enterprises are built. Manufacturing industry is developing: iron smelting, potash, glass and saltpeter.Domestic and foreign trade is expanding. Fairs, auctions and bazaars are organized and held. The number of shops, stores, stalls, etc. is growing. Merchants of various professions appear. Grain, cattle, potash, nitrate, flax, yarn, wool, and maple wood are sold at local and foreign markets. The city of Arkhangelsk is becoming an important center of Ukraine's foreign trade.Conclusiоns. The new economic system, which denied large-scale feudal land tenure, serfdom and serfdom, was formed in a fierce struggle for independence. The tsarist government tried at all costs to eliminate the autonomy of Ukraine, to restore feudal relations.
Keywords: economic policy, economic views, IS Mazepa, Cossack-peasant farms, crafts, handicrafts, agriculture